The Association of Dietary Vitamin Intake Time Across a Day With Cardiovascular Disease and All-Cause Mortality - Gu, Wenbo; Wu, Huanyu; Hu, Cong; Xu, Jiaxu; Jiang, Hongyan; Long, Yujia; Han, Tianshu; Yang, Xue; Wei, Wei; Jiang, Wenbo (Frontiers in Cardiovascular Medicine, 2022)
Background: Chrono-nutrition emphasized the importance of the intake-time; however, little is known about the impact of dietary-vitamin intake-time on health. The aim of this study was to examine our hypothesis which vitamin intake-time could influence the natural course of CVD. Methods: A total of 27,455 adults enrolled in the NHANES during 2003-2014 were recruited. The 12 dietary-vitamin intakes in the morning, afternoon, and evening, were respectively categorized into tertiles or quartiles. Cox-proportional hazards regression models were developed to evaluate the association of vitamin intake-time with CVD and all-cause mortality. Results：Compared to participants in the lowest quartile, participants in the highest quartile of dietary VB2 intake in the morning had significantly lowest mortality risk of CVD(HRVB2=0.75, 95%CI:0.60-0.94, p=0.017); whereas, participants in the highest quartile of dietary-VB6, VC, VE, and folate equivalent consumed in the evening showed the lowest mortality risks of CVD(HRVB6=0.77, 95%CI:0.60-0.99, p=0.103; HRVC=0.80, 95%CI:0.65-0.98, p=0.050; HRVE=0.75, 95%CI:0.56-0.99, p=0.032; HRfolate-equivalent=0.78, 95%CI:0.63-0.97, p=0.116) and all-cause(HRVB6=0.81, 95%CI:0.71-0.93, p=0.006; HRVC=0.85, 95%CI:0.76-0.95, p=0.004; HRVE=0.84, 95%CI:0.72-0.97, p=0.011; HRfolate-equivalent=0.80, 95%CI:0.71-0.90, p=0.001). Moreover, equivalently replacing 10% intake of dietary VB6, VC, VE and folate-equivalent in the morning with evening were associated with 4%(HRVB6=0.96, 95%CI:0.92-0.99), 5%(HRVC=0.95, 95%CI:0.92-0.99), 4%(HRVE=0.96, 95%CI:0.91-0.99) and 5%(HRfolate-equivalen=0.95, 95%CI:0.92-0.99) lower risk of CVD mortality. Conclusions: This study found that the optimal intake-time of dietary VB2 was in the morning, and optimal intake-times of dietary VB6, VC, VE, and folate equivalent were in the evening.